Stuck in division or passing through: What happens when cells cannot satisfy the spindle assembly checkpoint - Rieder, CL (2004)
The spindle assembly checkpoint (SAC) delays cells in mitosis when one or more kinetochore(s) cannot form a normal dynamic connection with microtubules (MTs). This occurs when spindle formation fails, or if it forms in the presence of one pole, aberrant centromeres/kinetochores, or MTs exhibiting abnormal dynamics. In the case of spindle poisons, the duration of the delay is influenced by the type of poison, its concentration, the cell species and type, and its resistance to the poison. When the SAC cannot be satisfied it is usually overridden. In yeast, this “adaptation” occurs via a pathway that inhibits cyclin B/CDK1. It is unknown if vertebrate cells adapt to the SAC by a similar process. The fate of a cell delayed in mitosis because it cannot satisfy the SAC varies depending on the type of drug (if a spindle poison was used), its concentration, the duration of the delay, when the cell was exposed to the insult and its genotype. Under extreme conditions cells that cannot satisfy the SAC die in mitosis by apoptosis or necrosis. However, under most conditions they exit mitosis and enter the next G1 as single 4N cells. Depending on the genotype, these cells can then either die by apoptosis, remain viable but undergo senescence, or re-enter the cell cycle. In the presence of functional spindles formed, e.g., when cells are delayed in mitosis by DNA damage or just one spindle pole, cells may divide to produce two or more aneuploidy progeny. Some of these may survive to generate neoplastic cells.